2013
DOI: 10.3109/14767058.2013.847916
|View full text |Cite
|
Sign up to set email alerts
|

Doppler flow parameters in orbital arteries in gestational diabetes mellitus patients

Abstract: Doppler examination can be useful in detection of pre-clinical ophthalmological changes in GDM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“… 50 , 51 , 56 , 63 Nevertheless, a recent study with Doppler technique in pregnant women with GDM demonstrated a decreased value for maximum diastolic velocity and resistance index in ophthalmic artery. 64 …”
Section: Resultsmentioning
confidence: 99%
“… 50 , 51 , 56 , 63 Nevertheless, a recent study with Doppler technique in pregnant women with GDM demonstrated a decreased value for maximum diastolic velocity and resistance index in ophthalmic artery. 64 …”
Section: Resultsmentioning
confidence: 99%
“…Doppler ultrasonography of orbital vessels is a valuable method that can aid in detection of subclinical changes impossible to diagnose by traditional methods. It is a noninvasive, relatively cheap and widespread tool . The ability of this technique to provide quantitative measurements of vascular flow opens up a new range of diagnostic possibilities, and allows statistical analysis with a greater degree of diagnostic discrimination in pathologies whose pathophysiology seems to involve vascular factors …”
Section: Introductionmentioning
confidence: 99%
“…It is a noninvasive, relatively cheap and widespread tool. 7 The ability of this technique to provide quantitative measurements of vascular flow opens up a new range of diagnostic possibilities, and allows statistical analysis with a greater degree of diagnostic discrimination in pathologies whose pathophysiology seems to involve vascular factors. 8 We questioned whether the vessels of the orbit may be affected in patients with psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…For the statistical analysis, the sample size was calculated in 200 patients with G*Power software (version 3.0.10; Heinrich‐Heine‐Universität, Düsseldorf, Germany), 14,18 adopting an effect size of f = 0.082, α error probability of .05, and test power of 0.95. The analyses were performed considering the 3 groups, with quantitative variables presented as the mean and standard deviation and qualitative variables as the frequency and percentage.…”
Section: Methodsmentioning
confidence: 99%
“…This study was justified by the need to describe the hemodynamic behavior of the OAs in pregnant women with pregestational DM with and without retinopathy to better understand the impact of hyperglycemia on the retinal vascular pattern. Based on this knowledge, prenatal follow‐up of pregnant women with pregestational DM may intensify, with a greater focus on the tracing and prediction of DR using several diagnostic methods such as an examination of the fundus of the eye by Doppler imaging of the orbital arteries 13,14 . The aim of this study was to evaluate ophthalmic Doppler velocimetric patterns in pregnant women with pregestational DM, with and without retinopathy, compared to pregnant women without gestational intercurrences.…”
mentioning
confidence: 99%